Retrospective cohort study of association of nsaids exposure and outcome of acute decompensated congestive heart failure - Wisuit Katekao (2018)
Background and Objective: Heart failure is a common medical disorder in elderly people. Previous studies have shown that non-steroidal anti-inflammatory drugs (NSAIDs) were considered to be associated with congestive heart failure (CHF) due to salt and water retention. However, there is limited data on NSAIDs-associated CHF in Thai population. The objective of the present study was to identify the significance of NSAIDs-related heart failure. Material and Method: This is a retrospective cohort study. Patient's medical records with the diagnosis of CHF between January 2008 and December 2009 were reviewed. The authors divided patients with CHF into two groups according to history of NSAIDs-exposure within a one year prior to admission. Baseline characteristics were compared and Kaplan--Meier analysis was used to determine survival difference. Results: One hundred ninety six CHF patients were included in the present study. NSAIDs-used within one year was confirmed in 47 patients (23.9%). Most of baseline characteristics were comparable for both groups. The major precipitating cause of CHF in NSAIDs-exposed group was statistically significant for acute coronary syndrome (40.4% vs. 14.8%, p-value <0.001), whereas anemia and renal failure failed to show statistical significance with p-value 0.859 and 0.370, respectively. Overall mortality showed no difference in both groups with p-value of 0.639. Conclusion: Previous studies considered NSAIDs to be associated with CHF due to salt and water retention. However, in the Thai population, there was an increasing incidence of acute coronary syndrome in concomitant with decompensated CHF. Overall mortality in both groups was not significantly different.